Chemical signatures of a warped protoplanetary disc. Issue 4 (11th June 2021) - Young, Alison K; Alexander, Richard; Walsh, Catherine; Nealon, Rebecca; Booth, Alice; Pinte, Christophe
ABSTRACT: Circumstellar discs may become warped or broken into distinct planes if there is a stellar or planetary companion with an orbit that is misaligned with respect to the disc. There is mounting observational evidence for protoplanetary discs with misaligned inner discs and warps that may be caused by such interactions with a previously undetected companion, giving us a tantalizing indication of possible planets forming there. Hydrodynamical and radiative transfer models indicate that the temperature varies azimuthally in warped discs due to the variable angle at which the disc surface faces the star and this impacts the disc chemistry. We perform chemical modelling based on a hydrodynamical model of a protoplanetary disc with an embedded planet orbiting at a 12° inclination to the disc. Even for this small misalignment, abundances of species including CO and HCO + vary azimuthally and this results in detectable azimuthal variations in submillimetre line emission. Azimuthal variations in line emission may therefore indicate the presence of an unseen embedded companion. Non-axisymmetric chemical abundances should be considered when interpreting molecular line maps of warped or shadowed protoplanetary discs.